Implementasi Media Pembelajaran Berbasis ICT dalam Proses Pembelajaran Matematika di Sekolah Menengah - Magdalena Wangge (Universitas Nusa Cendana, 2020)
For the presentation of the teachers' material more effectively and efficiently; therefore, it needs media learning that can motivate and stimulate students to morale in learning. One of them is by making use of ICT-based learning or media that we often call it TIK. This research aims to describe how the implementation of ICT-based learning media in learning mathematics in high school. This research is a research library. This research's nature is descriptive-i.e. decomposition analysis regularly, then the whole concept of giving comprehension and explanation to taste the result description. The analysis of the data used in this study analyzes the content (content analysis). The results of the research study this library is; (1) the existence of the benefits of ICT-based learning media in education; (2) the presence of the benefits of ICT-based learning media in the process of learning mathematics in high school.